DYNAMICS OF ANXIETY AND PERCEIVED STRESS AMONG THE PARTICIPANTS IN THE ХХV ANTARCTIC EXPEDITION - Galina Domuschieva-Rogleva; Tatiana Iancheva; Aleksander Shopov (Journal of Applied Sports Sciences, 2017)
The XXV Bulgarian Antarctic expedition on the Livingston isles, which included scientists and alpinists, began in November 2016. The participants’ activities are highly dependent on the extreme conditions they are in. The aim of the present research is to study dynamics of anxiety and perceived stress and to find a relation with the participants’ preferred strategies for coping with stress in highly risky activities in an extreme climatic and social environment. Subject of the study were 21 participants in the XXV Bulgarian Antarctic expedition, mean age 27 and 70. We have used Bulgarian adaptation of: Spielberger‘s Anxiety Inventory (STAI);Questionnaire for perceived stress (PS-1) and Coping Orientations to Problems Experienced scale – COPE 1. The first two tests were applied before the departure for Antarctica and before the return to Bulgaria. The level of perceived stress in the beginning of the expedition is significantly higher compared to the results obtained in the end of the expedition. Similar results were observed in terms of situational anxiety, which refers to the dynamic mental states. The cognitive engagement coping strategies are the main ones, whereas cognitive and emotional disengagement strategies are the least used. The results from the regression analysis show that the high levels of perceived stress has the biggest impact on the levels of anxiety in participants studied. The present study adds to the understanding the role of anxiety and perceived stress in difficult and challenging missions in extreme conditions in highly risky activities.